Efektivitas Program Pelatihan Berbasis Kompetensi Bagi Tenaga Kerja di Kabupaten Sidoarjo - Cahyani Marisa Wulandari; Sri Wibawani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The problem of unemployment in Sidoarjo Regency is currently a concern because of the high Open Unemployment Rate that occurs. The Sidoarjo Regency Manpower Office in reducing the high number of unemployed by holding competency-based training. The purpose of this training program is to improve the competence and competitiveness of the workforce and reduce the number of unemployed. This article aims to measure the effectiveness of the competency based training program for workers in Sidoarjo Regency. The research method uses a quantitative approach with data collection techniques using data collection tools in the form of questionnaires. The data analysis technique used is descriptive analysis. The results of the study indicate that the effectiveness of the implementation of the competencybased training program for workers in Sidoarjo Regency is in the fairly effective category on the indicator of increasing the competence and competitiveness of the workforce and on the indicator of reducing the number of unemployed, the majority are in a condition that starts from not working before participating in the training program to still not working after participating in competency based training.